2021
DOI: 10.1021/acsomega.1c01619
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations on the Interaction between Protein Tyrosine Phosphatase and E7 Oncoproteins of High and Low-Risk HPV: A Computational Perception

Abstract: The most prevalent and common sexually transmitted infection is caused by human papillomavirus (HPV) among sexually active women. Numerous genotypes of HPV are available, among which the major oncoproteins E6 and E7 lead to the progression of cervical cancer. The E7 oncoprotein interacts with cytoplasmic tumor suppressor protein PTPN14, which is the key regulator of cellular growth control pathways effecting the reduction of steady-state level. Disrupting the interaction between the tumor suppressor and the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…An IFD score those accounts for both the protein‐ligand interaction and total energy of the system were calculated which is further used to rank the IFD poses. Hence, the IFD protocol has been performed for the best data set compounds of the library with better docking scores and has emerged to be the common inhibitors for both virus 26,29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An IFD score those accounts for both the protein‐ligand interaction and total energy of the system were calculated which is further used to rank the IFD poses. Hence, the IFD protocol has been performed for the best data set compounds of the library with better docking scores and has emerged to be the common inhibitors for both virus 26,29 …”
Section: Methodsmentioning
confidence: 99%
“…Hence, the IFD protocol has been performed for the best data set compounds of the library with better docking scores and has emerged to be the common inhibitors for both virus. 26,29…”
Section: Induced Fit Dockingmentioning
confidence: 99%
“…E6 also contributes to the downregulation of the immune response against HPV by suppressing IFR3 (Interferon Regulatory Factor 3), a transcription factor for interferons (IFNs) ( 132 , 133 ), and by inhibiting IFNA (interferon alpha) interaction with its receptor ( 134 ). E7 acts synergically by inhibiting TLR9/CD289 (Toll-like receptor-9), present intracellularly in several immune cell types ( 135 , 136 ).…”
Section: Hpv Viral Components and Molecular Genetic And Epigenetic Me...mentioning
confidence: 99%
“…They identi ed small molecules and EGCG as potent inhibitors against the HPV 16 E7 oncoprotein. Furthermore, Aarthy and Singh [19] utilized a computational approach to explore the relationship between protein tyrosine phosphatase and E7 oncoproteins of high-and low-risk HPV. The ndings revealed that the LXCXE domain of HPV E7 at both high and low risk adheres to a tumor suppressor protein, and that certain compounds can interfere with the interaction between the oncoprotein and tumor suppressor at the E7-PTPN14 interface.…”
Section: Introductionmentioning
confidence: 99%